Selectivity of growth regulators and neonicotinoids for adults of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) - ANDRADE-CARVALHO, GERALDO; SEKIGUCHI-GODOY, MAURÍCIO; SILVA-PARREIRA, DOUGLAS; LASMAR, OLINTO; RODRIGUES-SOUZA, JANDER; FONSECA-MOSCARDINI, VALERIA (Revista Colombiana de Entomología, 2010)
The objective of this study was to evaluate the residual and sublethal effects of the insecticides acetamiprid (0.05 g a.i./L), lufenuron (0.04 g a.i./L), imidacloprid (0.14 g a.i./L), novaluron (0.02 g a.i./L), triflumuron (0.14 g a.i./L), and pyriproxifen (0.1 g a.i./L) on adults from the maternal generation of Trichogramma pretiosum, as well as their subsequent effects on the F1 and F2 generations. Eggs of Anagasta kuehniella were glued to paper cards, UV-killed, and dip-treated in insecticide solutions. Next, the eggs were exposed for parasitism 1, 24, and 48 h after treatment, maintained that way for 24 h under controlled conditions (24 ± 2°C, 70 ± 10% relative humidity, 12-h photophase), until the emergence of the parasitoids. The insecticide toxicity was calculated based on the longevity and parasitism capacity of the maternal generation, as well as on the emergence rate, sex ratio, longevity, and parasitism capacity of the F1 and F2 generations. The insecticides were toxicologically classified according to IOBC. Pyriproxifen was slightly harmful (class 2) for the parasitism capacity of T. pretiosum maternal and F generation females. Novaluron was slightly harmful for the emergence rate of the F1 generation. Acetamiprid, imidacloprid, lufenuron, and triflumuron were harmless (class 1) to T. pretiosum.